Incidence of Acute Neurological Events in Neonates and Infants Undergoing Cardiac Surgery Using a High-Hematocrit/ High-Flow Bypass Strategy. Issue 3 (May 2023) - Chakraborty, Abhishek; Ramakrishnan, Karthik; Buyukgoz, Cihangir; Tadphale, Sachin; Allen, Jerry; Absi, Mohammed; Briceno-Medina, Maria; Boston, Umar; Knott-Craig, Christopher J.
Background: The incidence of new acute neurological injury occurring in neonates and infants during cardiac surgery utilizing cardiopulmonary bypass is reportedly 3% to 5%. In 2013, we adopted a high flow rate, and high hematocrit bypass strategy, and sought to assess the incidence of early neurological injuries associated with this strategy.Methods: Neonates and infants undergoing cardiopulmonary bypass between January 2013 and December 2019 (n = 714) comprise the study. Adverse neurological events (ANEs) were defined as any abnormality of pupils, delayed awakening, seizures, focal neurological deficits, concerns prompting neurological consultation, or any abnormality on neurological imaging in the postoperative period. Our bypass strategy included a high flow rate (150-200 mL/kg/min), without reduction of flow rates during cooling and maintaining a target hematocrit on bypass > 32% with a terminal hematocrit of > 42%.Results: Median weight at the time of the procedure was 4.6 kg (IQR 3.6-6.1 kg) with the smallest patient weighing 1.36 kg. There were 46 premature patients (6.4%). There were 149 patients (20.9%) patients who underwent deep hypothermic circulatory arrest with a median time of 26 min (IQR 21-41 min). Hospital mortality was 3.5% (24/714, 95% CI: 2.28-5.13). The incidence of neurological events as defined above was 0.84% (6/714, 95% CI: 0.31-1.82). Neurological imaging identified ischemic injury in 4 patients and intraventricular hemorrhage in 2.Conclusions: High flow/high hematocrit bypass strategy was associated with a low incidence of ANE in this vulnerable population.